Pengaruh Tarif, Jam Kerja dan Jumlah Orderan Terhadap Pendapatan Driver Go-Jek di Kota Banjarmasin - Hartadi, Anggit Septiawan; Rusdiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to (1) analyze the effect of tariffs, working hours, and the number of orders on GO-JEK drivers' revenue in Banjarmasin City; (2) determine which factors predominantly influence the income of GO-JEK drivers in Banjarmasin City. This study indicates that tariffs and the number of orders individually (partially) and jointly (simultaneously) have a positive and significant effect on the revenue of GO-JEK drivers in Banjarmasin City. In contrast, working hours have a negative and insignificant impact on GO-JEK drivers' income in Banjarmasin City. The most dominant factor influencing GO-JEK driver revenue is a tariff.